Biomimetic MOF Nanocarrier‐Mediated Synergistic Delivery of Mitochondria and Anti‐Inflammatory miRNA to Alleviate Acute Lung Injury - Xin Shou; Changjiang Chen; Hangjie Ying; Zhiyun Liu; Lingyao Zeng; Qiujie Li; Lanjie Lei; Bingyong Mao; Wei Zhang; Shumao Cui; Liyun Shi (Advanced Science)
Abstract Acute lung injury (ALI) is a clinically critical disease characterized by overwhelming inflammatory response and significant tissue damage with no specific treatment available currently. As a key player in the pathogenesis of ALI, macrophages are aberrantly activated and polarize toward the pro‐inflammatory phenotypes, leading to overzealous inflammation and lung injury. Mitochondria is recognized as a crucial signaling hub governing macrophage function and polarization, deregulation of which is causatively related with defective metabolism of macrophages, deregulated inflammation, and hence ALI. Herein, an inflammation‐responsive, biomimetic metal‐organic framework (MOF) nanoplatform, termed a127/mito@ZIF@Ma is developed, which is sophistically designed for synergistic delivery of macrophage‐derived mitochondria and anti‐inflammatory miRNA‐127 antagonist to resume pulmonary macrophages homeostasis and alleviate lung inflammation and injury. Notably, macrophage membrane encapsulation conferred the biomimetic MOF with enhanced transport efficacy both in vitro and in vivo. Therefore, the administration of the nanoparticles accordingly conferred a profound protection of mice against lung inflammation and injury induced by either bacterial or viral infection with unnoticeable tissue toxicity. The study thus devises a novel MOF‐based nanosystem that integrates mitochondria transplantation and miRNA therapeutics, which may open a new avenue for treating ALI and relevant critical diseases.